PENGARUH PUPUK ORGANIK CAIR DAUN KELOR TERHADAPERTUMBUHAN BIBIT KARET (Hevea brasiliensis Muell. Arg)PADA TANAH PODSOLIK MERAH KUNING (PMK) - SITI Wulandari; Rika Fitry Ramanda; Venti Jatsiyah (Journal of Agro Plantation (JAP), 2026)
This study aimed to determine the effect of liquid organic fertilizer derived from moringa leaves on the growth of rubber seedlings (Hevea brasiliensis) grown in Ultisol (Red Yellow Podzolic) soil. The research was conducted at the Experimental Garden of Ketapang State Polytechnic from March to July 2024 using a non-factorial Completely Randomized Design with five treatment levels and four replications. The observed parameters included seedling height, stem diameter, number of leaves, root volume, and dry weight of seedlings. The results showed that the application of moringa leaf liquid organic fertilizer improved the growth of rubber seedlings across all observed parameters. The concentration of 500 mL/L produced the best results, with an average seedling height of 59.89 cm, stem diameter of 4.48 mm, number of leaves of 2.44, root volume of 7 mL, and dry weight of 9.40 g. This improvement is presumably due to the presence of essential nutrients and growth hormones in moringa leaves, which enhance soil properties and support plant physiological processes. Therefore, moringa leaf liquid organic fertilizer has the potential to be used as an alternative fertilization method to improve the quality of rubber seedlings in Ultisol soils.